Beyond perestroika : the future of Gorbachev's USSR - Mandel, Ernest; Fagan, Gus (London New York : Verso Verso, 1991)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Gorbatsjov, Michail; politiek beleid; Sovjet-Unie.